PERSEPSI PETANI SISTEM INTEGRASI TERHADAP PERAN LEMBAGAPENJAMIN DAN PENANGGUNG RESIKO DI KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN. - Manurung, Nuraini; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The development of cattle through the system of integration in the oil palm plantation area has great opportunity to be developed in the region, given the potential of oil palm plantations that are widely available, especially the people’s plantation. Crop livestock integration system is an agricultural system characterized by close association between crop components and livestock in a farming activity. The linkage is a trigger factor in encouraging farmer’s income growth and suistainable regional economic growth. This research was conducted in PangkalanLesung district of Pelalawan regency which aims to know the perception of farmers on the role of the guarantor institution and the risk bearer in supporting the SISKA program. The study was conduced from June to November 2017 using survey methods and intentional sampling techniques on government supported groups, while data analysis used Likert’s scale. The results showed that the perception of farmers on the role of insurers and risk insiders as a whole including the category less play with the average score of 2,12 which indicates that the role of the insurer and the risk is still not aptimally felt by the groupin supporting the development of SISKA seen from the primary production activity with a score of 2,79 including the category of enough role, product processing activities with a score of 1,78 including the category is very no role and marketing activities results with a score of 1,79 including the category very no role. Keywords :Perseption, institutions, risk, integration.